2014
DOI: 10.4103/1305-7456.137651
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between orthodontic treatment and gingival health: A retrospective study

Abstract: Objective:The aim of this retrospective study was to evaluate the relationship between orthodontic treatment and gingival health.Materials and Methods:A total of 251 patients among whom 177 were girls and 74 were boys, recruited from the records pool of the Department of Orthodontics, Faculty of Dentistry, University of Gazi, were included in the study. Patients’ treatments have been completed by postgraduate students during the period between 2006 and 2012. Patients’ folders were analyzed according to their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
7
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 24 publications
3
60
7
4
Order By: Relevance
“…When the gingival thickness of the maxillary anterior teeth was evaluated, it was found that gingival thickness of the canine teeth was lower than that of the central and lateral teeth, which is consistent with the results of the studies conducted by Younes et al (29) and Müller et al (30) Since permanent canine tooth germs, which are localized in the same direction with the roots of deciduous canine teeth, show vestibular eruption when there is no adequate space in the dental arch, it is known that these teeth have less alveolar bone, narrow keratinized gingiva, and lower gingival thickness (8,25,31,32).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…When the gingival thickness of the maxillary anterior teeth was evaluated, it was found that gingival thickness of the canine teeth was lower than that of the central and lateral teeth, which is consistent with the results of the studies conducted by Younes et al (29) and Müller et al (30) Since permanent canine tooth germs, which are localized in the same direction with the roots of deciduous canine teeth, show vestibular eruption when there is no adequate space in the dental arch, it is known that these teeth have less alveolar bone, narrow keratinized gingiva, and lower gingival thickness (8,25,31,32).…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, it was also observed that gingival thicknesses of tooth numbers 12 and 22 were greater in the severe crowding group than in the mild and moderate crowding groups. This was attributed to the greater amount of alveolar bone, wider keratinized gingiva, and increased gingival thickness due to the eruption of permanent lateral tooth germs, which are localized in the lingual aspect of the lateral deciduous teeth roots, without correcting their positions in the event of crowding (8,31,32 When incisor protrusion is planned, it is necessary to increase the gingival thickness with mucogingival surgical methods (13).…”
Section: Discussionmentioning
confidence: 99%
“…The increased buccolingual alveolar dimension from the augmentation bone grafting explains best the increased KT height. GR of the free gingival margin is another confounding variable in measuring KT height change, as shown by Boke et al, 26 who found a positive correlation between mandibular incisor position and GR in patients treated with fixed appliances and extraction. In the current investigation, clinical crown heights of mandibular incisors could not be measured from the photographs.…”
Section: Discussionmentioning
confidence: 97%
“…It has been known from the early work of Zachrisson that orthodontic treatment invariably results in a reduction in alveolar bone height. There is also concern regarding patient gingival health revealed by evidence that the lower canines have the highest incidence of gingival recession. In a study which had limited randomisation due to the nature of the subjects, a total of 35 patients, some with existing periodontal issues, were assessed.…”
Section: Periodontal Statusmentioning
confidence: 99%
“…A recent study compared two material systems (the ‘Nuvola ® ’ and the ‘Fantasmino ® ’ system) with differing material properties. Two groups of patients were respectively treated with Nuvola ® aligner and the following exclusion criteria were applied (a) Pre‐prosthetic orthodontic treatment (b) No extractions identified within the treatment plan and (c) No need for orthognathic surgery.…”
Section: Alignmentmentioning
confidence: 99%